Effect of cytokines on the epithelial function of the human colon carcinoma cell line HT29 cl 19A. Issue 5 (May 1993) - Hiribarren, A; Heyman, M; L'Helgouac'h, A; Desjeux, J F
Abstract : In various intestinal diseases, lymphoid cell infiltration of the lamina propria might be an important factor causing intestinal dysfunction through cytokine release. The effects of such cytokines were therefore measured on chloride secretion and macromolecular transport in intestinal HT29 cl 19A cells. Cells were grown on transwell filters and serosally exposed for two to 48 hours to 1% or 5% concentrations of phytohaemagglutinin (PHA) activated or non-activated healthy human mononuclear cell culture supernatants. These supernatants were tested for their interferon gamma (IFN gamma), tumour necrosis factor alpha (TNF alpha), and interleukin 6 (IL6) concentration. The mean (SE) were 4.72 (1.63), 3.17 (0.14), and 4.47 (1.12) ng/ml in activated supernatants. Intestinal function was studied in Ussing chambers: chloride secretion was assessed from the variations in short circuit current, and epithelial barrier capacity was monitored by the electrical resistance of the HT29 cl 19A cell monolayers and by measuring intact or degraded fluxes of the macromolecular tracer horseradish peroxidase. Release of lactate dehydrogenase (LDH) in the presence of various concentrations of cytokines was assessed as a test for cellular injury. The results indicate that serosal cytokines do not directly stimulate short circuit current. Long term (48 hours) exposure, however, significantly reduced both short circuit current (6.79 (0.65) v 2.90 (1.16) microA/cm2 in control v treated cells) and barrier capacity as shown by the decrease in resistance of the HT29 cl 19A cell monolayers from 158 (10) to 36 (9) ohms.cm2, and the increase in intact fluxes from 167 (33) in controls to 874 (206) ng/h.cm2, in cytokine rich supernatant treated cells and in degraded fluxes from 1113 (114) to 2327 (234) ng/h.cm2. This decreased barrier capacity was associated with an increase in release of LDH F(21.7 (1.2) and 43.6 (2.0) UI/h.cm2 in 1% and 5% cytokine treated monolayers v 10.8 (2.1) UI/h.cm2 in control monolayers). The results indicate that cytokines do not directly stimulate intestinal chloride secretion but that prolonged exposure to these agents reduced both electrolyte transport and barrier capacity to macromolecules through cellular and paracellular pathways.